The Influence Of Organizational Communication On Employee Performance on Seafood Trade Companies in Sidoarjo - Fariz Maulana; Sumartik Sumartik (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of transformational leadership style, organizational culture, organizational communication on employee performance with job satisfaction as an intervening variable at PT. Sekar Laut, Tbk. in Sidoarjo. This research is a type of quantitative research, the analytical tool used is tabulating the questionnaire. This study took a sample of 95 respondents and they are employees of PT. Sekar Laut, Tbk. in Sidoarjo. The method used in this research is (probability sampling), while the sampling technique uses (simple random sampling). Collecting data using a direct survey method with a questionnaire instrument. For further analysis using the method and analysis technique Partial Least Square (PLS) ± Structural Equation Model (SEM). The results showed that transformational leadership style had a significant effect on employee performance: organizational culture had a significant effect on employee performance: organizational communication had a significant effect on employee performance: Transformational leadership style had a significant effect on job satisfaction: Organizational culture had a significant effect on job satisfaction: Communication had a significant effect on job satisfaction. Job satisfaction: Transformational leadership style has a significant effect on employee performance through job satisfaction as an intervening variable: Organizational culture has a significant effect on employee performance through job satisfaction as an intervening variable: Organizational communication has a significant effect on employee performance through job satisfaction as an intervening variable: There is a significant influence on satisfaction work performance of employees.